The preliminary results of the differences in craniofacial and airway morphology between preterm and full-term children with obstructive sleep apnea - Yun-Chia Lian; Yu-Shu Huang; Christian Guilleminault; Kuang-Tai Chen; Michèle Hervy-Auboiron; Li-Chuan Chuang; Aileen I. Tsai (Elsevier, 2017)
Background/purpose: The prematurely born and obstructive sleep apnea (OSA) could affect craniofacial and airway growth. The purpose of this study is to compare the differences in craniofacial and airway morphology between preterm and full-term children both with OSA problem. Materials and methods: The differences in craniofacial and airway morphology between preterm children and full-term children both with OSA problem during the prepubertal (age 6-10) and pubertal (age 11-14) period were measured using lateral cephalometric radiograph. Results: In the prepubertal period, effective maxillary length, and length from Go to Gn were smaller in the preterm group (n = 6) compared to the full-term (n = 8). The length of the soft palate was smaller and the distance soft palate-posterior side of nasopharynx was longer in preterm children. During puberty, (1) position of maxilla relative to cranial base: there was an anteroposterior maxilla and a mandibular discrepancy, a convexity of facial profile, (2) the distance from point A to nasion perpendicular, the distance from Pog to nasion perpendicular, and the ratio of effective maxillary length/effective mandibular length were smaller in the preterm group (n = 5) compare to the full-term (n = 6). Conclusion: During prepuberty, the preterm children had a significantly shorter effective maxillary and mandibular length but the catch up growth resulted during the pubertal period in reduction in facial profile convexity and more important mandibular vertical growth toward a dolichocephalic profile. Due to preterm birth, OSA children have a different craniofacial morphology compared to the full-term. When using an oral device for passive myofunctional therapy, the treatment outcome maybe different. Keywords: preterm children, obstructive sleep apnea, craniofacial and airway morphology